2019
DOI: 10.1007/s42452-019-0451-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural dependent, dielectric and conduction analysis of CdSe based quantum dots

Abstract: Nowadays, the effect of temperature on nanocrystal's dielectric has become a routine study while their structural effects on dielectric properties, lacks the attention of researchers. The correlation of different shell arrangement on dielectric enhancement in CdSe based quantum dots, is addressed in this letter. Detrimental impact of surface defects on dielectric properties of quantum dots is investigated and shown that surface defects of bare core increases dielectric loss, dissipation factor and decreases co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Experimentally, there have been several synthesis methods have been developed for group-II chalcogenide compounds, including colloidal approach 38 , colloidal ALD 39 , chemical bath deposition 40 , CVD 41 . Their unique properties have been revealed by a lot of theoretical cal-culations and analytical methods [42][43][44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, there have been several synthesis methods have been developed for group-II chalcogenide compounds, including colloidal approach 38 , colloidal ALD 39 , chemical bath deposition 40 , CVD 41 . Their unique properties have been revealed by a lot of theoretical cal-culations and analytical methods [42][43][44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%
“…Fig. (6 a) acts the real part of the dielectric constant ε 1 since the dielectric constant determines the number of polarized atoms optically towards the internal electric field, it was observed that ε1 appears to be constant in this range of wavelengths That is the determination of the number of polarized atoms towards the internal electric field [35]. On the other hand, since the smallest quantum dots contain fewer atoms, that is, the atoms that are affected by the optical polarization will in any way be less.…”
Section: Resultsmentioning
confidence: 99%
“…The nanoscale semiconductor heterostructures amd for instance core/shell quantum dots (QDs) with diameters smaller than the bulk exciton Bohr radius are new class of materials intermediates between molecular and bulk solid forms. CdSe based core-shell type quantum dots (QDs) exhibit novel properties making them attractive from both experimental and theoretical point of view [5][6][7][8][9][10][11][12]. It has been shown that coating core semiconductor with larger band gap of its kind, improve properties of nanocrystals (NCs) [13,14].…”
Section: Introductionmentioning
confidence: 99%